2018
DOI: 10.29252/jrh.8.4.322
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Spirituality and sensation seeking with tanatophobia in hemodialysis patients

Abstract: Background: HIV Positive or AIDS is a complex disease that weakens the immune system and causes infection. Moreover, since in most societies it is known as a social taboo, all aspects of a patient's life being particularly affected with HIV. Also, AIDS is not only a health issue but also a social problem as well. The aim of this study was to evaluate the effectiveness of spiritual treatment on quality of life and life satisfaction in patients with AIDS. Methods: This semi-experimental study performed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Consistent with these findings, Askarizadeh et al . [ 27 ] showed that attempting to promote the individuals' spiritual well-being and sensation-seeking can play an important role in reducing the death anxiety. In another study, Cooper[ 28 ] showed that a priest, who had been trained on cancer, could improve the patient's distress, especially in relation with death anxiety, mental peace and health, and meaning of life.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, Askarizadeh et al . [ 27 ] showed that attempting to promote the individuals' spiritual well-being and sensation-seeking can play an important role in reducing the death anxiety. In another study, Cooper[ 28 ] showed that a priest, who had been trained on cancer, could improve the patient's distress, especially in relation with death anxiety, mental peace and health, and meaning of life.…”
Section: Discussionmentioning
confidence: 99%